The self-help compulsion : searching for advice in modern literature - Blum, Beth (Columbia University Press, 2020)
"Blum explores popular reading practices in which people turn to literature in search of practical advice alongside modern writers' rebukes of such instrumental purposes. As literary authors positioned themselves in opposition to people like Samuel Smiles and Dale Carnegie, readers turned to self-help for the promises of mobility, agency, and use that serious literature was reluctant to supply. Blum unearths a series of unlikely cases of the love-hate relationship between serious fiction and commercial advice, from Gustave Flaubert's mockery of early DIY culture to Dear Abby's cutting diagnoses of Nathanael West and from Virginia Woolf's ambivalent polemics against self-improvement to the ways that contemporary global authors such as Mohsin Hamid and Tash Aw explicitly draw on the self-help genre. She traces the self-help industry's tendency to quote, repurpose, and adapt literary wisdom and considers what self-help might have to teach today's university. Offering a new account of self-help's origins, appeal, and cultural and literary import around the world, this book reveals that self-help's most valuable secrets are not about getting rich or winning friends but about how and why people read" --